Is part-time employment beneficial for firm productivity? - Annemarie Nelen; Andries de Grip; Didier Fouarge (Institute for the Study of Labor (IZA), 2011)
This paper analyzes whether part-time employment is beneficial for firm productivity in the service sector. Using a unique dataset on the Dutch pharmacy sector that includes the work hours of all employees and a hard physical measure of firm productivity, we estimate a production function including heterogeneous employment shares based on work hours. We find that a larger part-time employment share leads to greater firm productivity. Additional data on the timing of labor demand show that part-time employment enables firms to allocate labor more efficiently. First, firms with part-time workers can bridge the gap between opening hours and a full-time work week. Second, we find that during opening hours part-time workers are scheduled differently than full-timers. For example, we find that part-time workers enable their full-time colleagues to take lunch breaks so that the firm can remain open during these times.
urn:nbn:de:101:1-201104084342
Keywords: J24; L23; L25; 330; heterogeneous labor; matched employer-employee data; allocation of labor; timing of labor demand; Teilzeitarbeit; Produktivität; Arbeitsnachfrage; Dienstleistungssektor; Pharmazeutische Industrie; Niederlande